2018
DOI: 10.1111/evo.13647
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the relative contributions of the X chromosome, autosomes, and mitochondrial genome to local adaptation*

Abstract: During local adaptation with gene flow, some regions of the genome are inherently more responsive to selection than others. Recent theory predicts that X‐linked genes should disproportionately contribute to local adaptation relative to other genomic regions, yet this prediction remains to be tested. We carried out a multigeneration crossing scheme, using two cline‐end populations of Drosophila melanogaster, to estimate the relative contributions of the X chromosome, autosomes, and mitochondrial genome to diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 86 publications
(193 reference statements)
1
22
0
Order By: Relevance
“…; Lasne et al. ), studies conducted since The Millenial Drought (1996–2010) have reported elevated desiccation resistance in temperate populations from southeastern Australia, where desiccation stresses have been particularly intense (Lasne et al., , ; the current study). In light of these observations, our four focal traits are among the best candidates for adaptive divergence by latitude across eastern Australia.…”
mentioning
confidence: 48%
See 1 more Smart Citation
“…; Lasne et al. ), studies conducted since The Millenial Drought (1996–2010) have reported elevated desiccation resistance in temperate populations from southeastern Australia, where desiccation stresses have been particularly intense (Lasne et al., , ; the current study). In light of these observations, our four focal traits are among the best candidates for adaptive divergence by latitude across eastern Australia.…”
mentioning
confidence: 48%
“…Australian Drosophila populations have played a key role in studies of climatic adaptation, repeatedly exhibiting genetically based clinal divergence in body size and thermal stress traits, despite strong gene flow across the cline (Kennington et al 2003;Hoffmann and Weeks 2007;Sgrò et al 2010;Hangartner et al 2015;Lasne et al 2018). Although desiccation resistance has shown less consistent clinal divergence than our other focal traits (Hoffmann et al 2001;Lasne et al 2018), studies conducted since The Millenial Drought (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010) have reported elevated desiccation resistance in temperate populations from southeastern Australia, where desiccation stresses have been particularly intense (Lasne et al, 2018(Lasne et al, , 2019; the current study). In light of these observations, our four focal traits are among the best candidates for adaptive divergence by latitude across eastern Australia.…”
mentioning
confidence: 87%
“…Recently, sometimes unexpected complexity of sex chromosome markers has been highlighted ( cf . Lasne, van Heerwaarden, Sgrò, & Connallon, 2018; Battey, 2020; Hayes, Barton, & Zeng, 2020). This system offers much to the study of the genomics of differentiation and speciation.…”
Section: Discussionmentioning
confidence: 99%
“…Lasne et al. () explore this problem by investigating trait variation in two divergent populations of Drosophila melanogaster from each end of the eastern Australian latitudinal cline. First, they construct a series of theoretical models to create predictions about the contribution of mitochondrial, autosomal, and sex chromosomes to adaptive trait divergence given different patterns of dispersal and variation in population size and selection strength.…”
mentioning
confidence: 99%
“…Although recent work has made predictions about the importance of different genomes for adaptation, namely, the mitochondrial genome (e.g., Camus et al 2017), there is little experimental evidence available for the relative contributions of autosomal chromosomes, sex chromosomes, and mitochondrial genomes to adaptive trait divergence and local adaptation. Lasne et al (2019) explore this problem by investigating trait variation in two divergent populations of Drosophila melanogaster from each end of the eastern Australian latitudinal cline. First, they construct a series of theoretical models to create predictions about the contribution of mitochondrial, autosomal, and sex chromosomes to adaptive trait divergence given * This article corresponds to Lasne, C., B.…”
mentioning
confidence: 99%